PHENOMENOLOGICAL SIGNS OF CONSTITUTIONAL TYPOLOGICAL FAILURE IN PRESCHOOLERS - Natalia Viktorovna Cherepkova (Вестник Северо-Кавказского федерального университета, 2022)
In the article the author examines the specific results of the study on the study of the phenomenological characteristics constitutional typological deficiency in children of preschool age, depending on the constitutional and typological features.